Intra‐Annual Variation of Eddy Diffusion (kzz) in the MLT, From SABER and SCIAMACHY Atomic Oxygen Climatologies. Issue 23 (6th December 2021) - Swenson, G. R.; Vargas, F.; Jones, M.; Zhu, Y.; Kaufmann, M.; Yee, J. H.; Mlynczak, M.
Abstract: Atomic oxygen (O) in the mesosphere and lower thermosphere (MLT) results from a balance between production via photo‐dissociation in the lower thermosphere and chemical loss by recombination in the upper mesosphere. The transport of O downward from the lower thermosphere into the mesosphere is preferentially driven by the eddy diffusion process that results from dissipating gravity waves and instabilities. The motivation here is to probe the intra‐annual variability of the eddy diffusion coefficient (k zz ) and eddy velocity in the MLT based on the climatology of the region, initially accomplished by Garcia and Solomon (1985, https://doi.org/10.1029/JD090iD02p03850 ). In the current study, the intra‐annual cycle was divided into 26 two‐week periods for each of three zones: the northern hemisphere (NH), southern hemisphere (SH), and equatorial (EQ). Both 16 years of SABER (2002–2018) and 10 years of SCIAMACHY (2002–2012) O density measurements, along with NRLMSIS ® 2.0 were used for calculation of atomic oxygen eddy diffusion velocities and fluxes. Our prominent findings include a dominant annual oscillation below 87 km in the NH and SH zones, with a factor of 3–4 variation between winter and summer at 83 km, and a dominant semiannual oscillation at all altitudes in the EQ zone. The measured global average k zz at 96 km lacks the intra‐annual variability of upper atmosphere density data deduced by Qian et al. (2009, https://doi.org/10.1029/2008JA013643 ). The very large seasonal (and hemispherical) variations in k zz and O densities are important to separate and isolate in satellite analysis and to incorporate in MLT models. Key Points: Intra‐annual variations (IAVs) of k zz in the MLT, from SABER and SCIAMACHY atomic oxygen climatologies are determined Deduced k zz values at mid‐latitudes have a prominent annual oscillation below 87 km, while equatorial values vary semiannually (80–96 km) Hemispherical IAVs (seasonal) in k zz and O density dominate the MLT, contrary to the global averages used currently in some GCMs